Marchés obligataires et crises bancaires dans les pays émergents: le rôle des institutions: Bond Markets and Banking Crises in Emerging Market Economies: The Role of Institutions - Boukhatem, Jamel (Panoeconomicus, 2012)
This paper deals with the question of knowing if countries whose activity of financing is mainly bank based face crises more expensive than those where the bond markets are broader and more developed. The results of the empirical tests on a panel of emerging countries suggest that bank based financial systems are associated with crises slightly more expensive, whereas the relationship between the bond markets and the crises’ costs is fragile. Moreover, financial systems where bond markets play an important role are associated with a higher growth of the production, and this, independently of the presence or not of crises. The consideration of the combined effect of financial liberalization and institutional framework on the bond markets development shows the importance of the direction of the financial liberalization. We join in this case one of the most significant aspects of the “sequencing” theorized by McKinnon (1973). Finally, an effective prudential regulation tends to reduce significantly the probability of occurrence of banking crises. Mots clés: Financement obligataire, Financement bancaire, Crises bancaires, Données de panel. Key words: Bond financing, Bank financing, Banking crisis, Panel data. JEL: E44, G0, G21.